Improving the effectiveness of serves by elite volleyball players through the differentiation of muscular effort - Lutkova, N.V.; Makarov, Yu.M.; Panchenko, I.A.; Vasiliev, D.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to improve the effectiveness of the serve among elite volleyball players by developing their ability to precisely modulate muscle effort through the use of specialised exercise programmes. Methods and structure of the study. Serve performance indicators were assessed based on competition data: for the main team ‘Dynamo-LO’ – in the Russian Men’s Volleyball Championship, and for the reserve team ‘Dynamo-LO-2’ – in the Russian Youth League. Parameters characterising technique, situational conditions and the direction of serves among skilled volleyball players were analysed. 10 matches involving leading teams were analysed using the professional software Data Volley 4Pro. The athletes’ baseline fitness level was determined through pedagogical testing. The ability to differentiate muscle effort was assessed using a DK-140 hand dynamometer, which allowed for the measurement of the accuracy of reproducing specified force levels (25%, 50%, 75% of maximum effort). The experimental part included specialised exercise blocks aimed at developing upper body strength and force discrimination sensitivity. 24 qualified volleyball players took part in the study. Results and conclusions. It was established that the qualified volleyball players of the ‘Dynamo-LO 2’ team perform a placement serve more frequently than a power serve during competitive play. The performance indicators of the skilled volleyball players from the ‘Dynamo-LO-2’ team show statistically significant differences from those of the players from the ‘Dynamo-LO’ team across all six analysed characteristics. It was found that it is advisable to identify four narrowly focused sets of exercises for developing the ability to differentiate muscle effort (using TRX loops, resistance bands, medicine balls and volleyballs). Among the skilled volleyball players of the ‘Dynamo-LO-2’ team, a positive trend was observed in the number of placement and power serves, the effectiveness of their execution, and a reduction in the number of errors during their execution.